Influence of the phase balance and cooling conditions on the microstructure and corrosion behavior of solution-treated 1.4462 duplex stainless steel - Yalciner, Guluzar; Ozer, Gokhan; Kisasoz, Alptekin; Karaaslan, Ahmet (IOP Publishing Ltd, 2019)
In this study, effect of cooling rate on the microstructure and corrosion behavior of the solution-treated 1.4462 alloy was investigated. 1.4462 alloy was heat-treated at 1000 degrees C, 1120 degrees C and 1200 degrees C for different duration in order to obtain various phase balance. Two different cooling regimes (rapid cooling and steady cooling) were applied following the solution treatment processes. Also, effect of sigma phase was investigated together with ferrite and austenite phases for steady cooled samples. After heat treatment processes, samples were characterized by an optical microscope (OM), image analysis and scanning electron microscope (SEM). Moreover, hardness tests and electrochemical corrosion tests were applied. According to results, Ferrite ratio and ferrite grain size were increasing with increasing solution treatment temperature and time. Also, ferrite phase was more dominant compared to sigma phase for hardness of the solution-treated samples. Moreover, existing of sigma in higher amount promoted the observation of Epit value.
Keywords: duplex stainless steel; 1.4462 alloy; solution treatment; corrosion resistance; SIGMA-PHASE; ANNEALING TEMPERATURE; MECHANICAL-PROPERTIES; PITTING CORROSION; PRECIPITATION; RESISTANCE; Materials Science